2012
DOI: 10.1113/jphysiol.2012.237644
|View full text |Cite
|
Sign up to set email alerts
|

Gβ2 and Gβ4 participate in the opioid and adrenergic receptor‐mediated Ca2+ channel modulation in rat sympathetic neurons

Abstract: Key point• Sympathetic stellate ganglion (SG) neurons that innervate cardiac muscle play an important role in regulating heart rate and contractility.• In this study, we examined which Gβ protein subunit couples Ca 2+ channels to opioid and adrenergic receptors expressed in SG neurons.• We show that Gβ2 and Gβ4 are important signalling elements that maintain the transduction pathway of both receptor subtypes and Ca 2+ channels, and how their expression levels are differentially compensated.• Our results also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…In a separate study aimed at identifying the subunit composition of the G protein coupled to M1-muscarinic acetylcholine receptors, it was shown using antisense oligonucleotides in rat basophilic leukemia RBL-2H3-hm1 (rat basophilic leukemia cell line) cells, that the loss of Gb 1 and Gb 4 reduced carbacholmediated Ca 2+ release (Dippel et al, 1996). Gb 2 and Gb 4 knockdown with siRNA demonstrated that these two Gb subunits mediate coupling of adrenergic and nociceptin receptors to voltage-gated calcium channels in stellate ganglion neurons (Mahmoud et al, 2012).…”
Section: Phenotypes Associated With Knockout and Knockdown Of Gb mentioning
confidence: 99%
“…In a separate study aimed at identifying the subunit composition of the G protein coupled to M1-muscarinic acetylcholine receptors, it was shown using antisense oligonucleotides in rat basophilic leukemia RBL-2H3-hm1 (rat basophilic leukemia cell line) cells, that the loss of Gb 1 and Gb 4 reduced carbacholmediated Ca 2+ release (Dippel et al, 1996). Gb 2 and Gb 4 knockdown with siRNA demonstrated that these two Gb subunits mediate coupling of adrenergic and nociceptin receptors to voltage-gated calcium channels in stellate ganglion neurons (Mahmoud et al, 2012).…”
Section: Phenotypes Associated With Knockout and Knockdown Of Gb mentioning
confidence: 99%
“…The DRG tissue was transfected with small interference RNA (siRNA) using electroporation and lipofection, as described previously (Mahmoud et al 2012). Briefly, once L 4 -L 6 DRG tissue was removed, it was first electroporated with the Neon electroporator (Life Technologies, Carlsbad, CA) with three 1,000-V pulses for 20 ms duration in an electroporation solution, which consisted of R solution (Life Technologies), scrambled or G␣-targeted siRNA (3,000 nM; Life Technologies), and 2 mM 2,3-butanedione monoxime (BDM).…”
Section: Methodsmentioning
confidence: 99%
“…SG neurons were transfected with siRNA employing both electroporation and lipofection as previously described [11]. Gγ7 subunit siRNA sequences designed in this study were chosen based on an eight point criteria with a scoring system (10 = best, 1 = worse) [17].…”
Section: Methodsmentioning
confidence: 99%
“…Following the transfection period, the SG tissue was enzymatically dissociated as previously described [11]. Briefly, the tissue was incubated in a shaking water bath (35°C) for 60 min in Earle's balanced salt solution containing 0.6 mg/ml collagenase Type D (Roche Diagnostics, Indianapolis, IN), 0.4 mg/ml trypsin (Worthington Biochemicals, Freehold, NJ) and 0.1 mg/ml DNase (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation